Evaluation of thiol levels, thiol/disulfide homeostasis and their relation with inflammation in cardiac syndrome X. Issue 4 (June 2016) - Altiparmak, Ibrahim H.; Erkus, Muslihittin E.; Sezen, Hatice; Demirbag, Recep; Kaya, Zekeriya; Sezen, Yusuf; Gunebakmaz, Ozgur; Asoglu, Ramazan; Besli, Feyzullah; Neselioglu, Salim; Erel, Ozcan
Abstract : Objectives: Cardiac syndrome X (CSX) is characterized by the presence of myocardial ischemia in the absence of coronary artery stenosis on angiograms. Its relation to oxidative stress and inflammation is well known. There are no data on thiols and their relation with inflammation in CSX. The aim of this study was to investigate thiol levels and thiol/disulfide homeostasis in CSX patients. Materials and methods: Fifty consecutive patients who had documented myocardial ischemia and normal coronary angiogram (CSX group), and 45 age-matched and sex-matched consecutive patients who had normal coronary angiogram without myocardial ischemia (control group) were enrolled in this study. C-reactive protein (CRP), neutrophil/lymphocyte ratio (NLR), native thiol, total thiol, and disulfide levels were measured and disulfide/thiol ratios were calculated in all patients. Results: Demographic, clinical, basic laboratory, and echocardiographic characteristics were similar in the two groups ( P >0.05). Serum total thiol, native thiol, and disulfide levels decreased significantly in the CSX group compared with the control group ( P <0.001). CRP and NLR increased significantly in the CSX group compared with the control group ( P <0.001). Although disulfide/native thiol levels increased in the CSX group, this reduction did not reach statistical significance (5.8 vs. 5.5, P >0.05). The reduction of thiols was correlated negatively with CRP and NLR ( P <0.001). Although univariate logistic regression analyses showed that serum total and native thiol levels, CRP and NLR were independent predictors for CSX estimation, stepwise multivariate logistic regression analysis showed only total thiol levels as an independent predictor for CSX (odds ratio=0.966, 95% confidence interval: 0.950–0.982, P <0.001). Also, receiver operating characteristic curve analysis showed that serum total thiol values of 338.4 or below could predict the CSX with 86% sensitivity and 84% specificity (area under curve=0.903; 95% confidence interval: 0.842–0.965). Conclusion: Serum total thiol levels decreased significantly in CSX and this reduction independently predicted CSX with strong sensitivity and specificity. This suggests that the reduction in thiols along with increased inflammation may play a pathophysiological role in the development of CSX.